ONLINE PEER MENTORING TO ENHANCE MATHEMATICAL PROBLEM-SOLVING STRATEGY AMONG INTROVERT AND EXTROVERT PERSONALITY - Wan Norliza Wan Bakar (Jurnal Penyelidikan Sains Sosial, 2021)
Mathematical problem solving is a process of constructing a mathematical model and devising strategies to solve mathematical problems. There are many factors affected student’s ability in problem solving. Personality is one of them. Due to this factor, a qualitative study is carried out on online peer mentoring in problem strategy among introvert and extrovert personality. 40 students participated. They have undergone (Myer Briggs Personality Test) and the students are classified under 8 groups which consists of introvert and extrovert. After answering the paper, the students were interviewed. The result of the study shows that online peer mentoring for introvert and extrovert enhance the ability of the students in their performance.